Analisis Pendapatan Dan Kelayakan Finansial Usaha Penggemukan Domba di Desa Pulosari Kecamatan Telagasari Kabupaten Karawang - Nur’azizah, Ismi; Muharam, Muharam; Sulandjari, Kuswarini (Jurnal Ilmiah Wahana Pendidikan, 2025)
Sheep, as one type of small ruminant that has become a popular herbivorous animal among breeders. To encourage the development of livestock business, an analysis was carried out to find the business feasibility of farmers in Pulosari Village. The research method used is quantitative descriptive with the use of primary data. Primary data were collected through interviews using questionnaires. Business feasibility analysis techniques are carried out by calculating production costs, revenues, revenues, break even points (BEP), and R/C ratios. The results showed that the average cost incurred for 6 months was Rp. 43,040,609, while the average revenue was Rp. 57,688,148 and the average income was Rp. 14,647,539 during the same period. The break-even point (BEP) price is Rp. 2,198,657 per head with BEP production of 15.58 heads. The results of the feasibility analysis show that the sheep fattening business is feasible to be developed, with an R/C Ratio value of 1.28.